Statins on Spontaneous Intracerebral Hemorrhage: A Meta-Analysis. (9th August 2022) - Liu, Xiaojiao; Luo, Wenxiu; Huang, Hua; Fan, Jin
Abstract : Objective . In order to explore whether the application of statins can improve the prognosis of patients with intracerebral hemorrhage. Methods . Studies of patients with intracerebral hemorrhage taking statins published in English until December 2021 were searched based on limited search terms, the retrieved literature was screened out based on inclusion and exclusion criteria, and the quality assessment and data extraction were carried out independently by two investigators. The extracted clinical data were then meta-analyzed. Results . A total of 17 literatures were included in this study, with a sample size of 16, 988 cases, including 3, 001 cases in the statin group and 13, 487 cases in the control group. MRS score of mortality was used as the prognostic index to evaluate cerebral hemorrhage. According to the Newcastle-Ottawa Scale (NOS), the score of literature quality evaluation scale was 6–8, indicating good literature quality. Meta-analysis of clinical data extracted from the literature showed that the statin group reduced overall mortality after intracerebral hemorrhage compared with the nonstatin group (P < 0.01 ). In terms of improving functional prognosis, the statin group improved functional prognosis 90 days after intracerebral hemorrhage (P = 0.01 ). There was no significant difference between the statin and nonstatin groups in reducing the number of intracerebral hematomas. Conclusions . Statins can reduce the total mortality after ICH and improve the survival rate (90 d), without increasing the amount of hematoma.